2021
DOI: 10.1084/jem.20210554
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting autoantibodies to type I IFNs underlie critical COVID-19 pneumonia in patients with APS-1

Abstract: Patients with biallelic loss-of-function variants of AIRE suffer from autoimmune polyendocrine syndrome type-1 (APS-1) and produce a broad range of autoantibodies (auto-Abs), including circulating auto-Abs neutralizing most type I interferons (IFNs). These auto-Abs were recently reported to account for at least 10% of cases of life-threatening COVID-19 pneumonia in the general population. We report 22 APS-1 patients from 21 kindreds in seven countries, aged between 8 and 48 yr and infected with SARS-CoV-2 sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
240
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 236 publications
(258 citation statements)
references
References 59 publications
12
240
0
6
Order By: Relevance
“…On day 6 after symptom onset, he developed fever (Tmax 39.5°C) and became hypoxic with SpO2 of 91% ( Figures 1A, B ) and PaO2 of 63 mmHg necessitating supplemental oxygen (2 liters/min by nasal cannula). Because corticosteroids decrease COVID-19–associated hyper-inflammation and improve survival ( 27 ) and initiation of corticosteroids within 24 hours of hypoxemia onset was associated with improved outcomes in APECED patients ( 13 ), we initiated methylprednisolone (0.5 mg/Kg/day) on day 6 after symptom onset. Fever and cough resolved by day 8 after symptom onset.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On day 6 after symptom onset, he developed fever (Tmax 39.5°C) and became hypoxic with SpO2 of 91% ( Figures 1A, B ) and PaO2 of 63 mmHg necessitating supplemental oxygen (2 liters/min by nasal cannula). Because corticosteroids decrease COVID-19–associated hyper-inflammation and improve survival ( 27 ) and initiation of corticosteroids within 24 hours of hypoxemia onset was associated with improved outcomes in APECED patients ( 13 ), we initiated methylprednisolone (0.5 mg/Kg/day) on day 6 after symptom onset. Fever and cough resolved by day 8 after symptom onset.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, patients with genetic defects in type-I IFN pathways or neutralizing autoantibodies directed against type-I IFNs, including APECED patients, are among those carrying a high risk for severe disease. A recent study describing the clinical course of 22 APECED patients with COVID-19 showed higher rates of ICU admission (68%), mechanical ventilation (50%) and death (18%) ( 13 ). The study suggested that therapeutic modalities aimed at early augmentation of viral clearance (IFN-β, remdesivir), lowering of type-I IFN autoantibody titers (plasmapheresis), and early initiation of corticosteroids upon hypoxemia onset may help improve patient outcomes ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it was shown that some patients with life-threatening COVID-19 had neutralizing IgG auto-antibodies against IFN-ω, IFN-α, or both. These antibodies prevent the corresponding type I IFNs from blocking SARS-CoV-2 infection in vitro and were preferentially found in patients with severe COVID-19 [ 575 , 576 , 577 , 578 ]. Altogether, these data strongly support the notion that dysregulated type I IFN immunity underlies life-threatening COVID-19 pneumonia.…”
Section: Cytokines and Innate Immune Responsementioning
confidence: 99%